Sociological Study of Islamic Law on the Phenomenon of the Gredoan Tradition in the Osing Banyuwangi Community - Wagianto, Ramdan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This article discusses the phenomenon of the gredoan tradition that occurs in the Osing Banyuwangi community. This tradition, which is usually carried out on the eve of the Prophet Muhammad's birthday, is used as an opportunity for young people or widowers and widows to find a soul mate or life partner. The aim of this research is to find out and describe the phenomenon of the gredoan tradition in the Osing Banyuwangi community and the sociological perspective of Islamic law in looking at the tradition phenomenon that occurs. The research method is qualitative, using a sociological approach and Islamic law. The results of the research show that the Gredoan tradition can be said to be a local ta'aruf which uses the basis of customs and culture in the Osing Banyuwangi community. This gredoan tradition is carried out on the eve of the birthday of the Prophet Muhammad SAW. The process is first, young men or widowers carry out gridu on women using sodho or sticks which are then inserted into the hole in the wall of the gedheg. Then the woman who was grieved will respond by breaking the sodho or returning the sodho. The gesture of breaking the sodho means acceptance and returning the sodho contains a gesture of rejection. Second, is ngeleboni, as an attempt by the male perpetrator to stay in touch with the woman's parents. Third, munggah kawen is the stage that is the peak goal of gredoan. The Gredoan tradition is classified as urf sahih. This is because in this tradition there are no deviations from the Quran and Hadith, in fact this tradition can bring benefits to society in the context of finding a soul mate.